Effect of approach run velocity on the optimal performance of the triple jump - Yu, B.; Liu, H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to determine the effect of approach run velocity on the optimal phase ratio and actual distance of the triple jump. Three-dimensional kinematic data of 13 elite male triple jumpers were obtained. Computer simulations were performed using a biomechanical model of the triple jump to optimize the phase ratio for the longest actual distance with different approach run velocity vectors. As horizontal velocity increased, the actual distance and jump percentage increased while the hop percentage decreased. As the vertical landing velocity increased, the actual distance, hop percentage, and jump percentage decreased. As the velocity conversion coefficient increased, the effect of vertical landing velocity of approach run on the optimal performance increased.